Folkevandringstidens dyreornamentikk i Sørvestnorge - Kristoffersen, Siv (Hikuin, 2002)
Migration-Period Animal Ornament in South-Western Norway By Siv Kristoffersen Southern and western Norway, the regions from Vestfold to Sogn og Fjordane, is a leading area for the distribution of Migrationperiod animal art (fig. 1). This paper discusses the characteristics and regional distribution of both the Nydam Style and Style I, and their archaeological and social contexts. The relation of the styles to political processes in the period is also touched upon. There are 98 finds involving 137 gilded objects decorated with these styles. The frequency of objects increases during the Migration Period and is by far the greatest in the last phase (tab. 1). Important pieces with the Nydam-style are found in Vestfold, at Lista, and in Jæren, such as the relief brooches in finds F3, F25 and F47 (fig. 1). Characteristic local traditions of Style I are also found in Vest- Agder/Rogaland (the area of F16-F62) and in Sogn og Fjordane (the area of F80-F93). 83 finds are from burials. Most of these were found under mounds, usually large ones. The majority were inhumation burials in stone cists. They were richly furnished, many including gold and silver objects as well as imported glass and bronze vessels. There is variation however, especially in the latest phase. Skeletons are rarely preserved. Two categories of burial are distinguished: burials with weaponry (14) and burials with relief brooches (42). Relief brooches are often combined with smaller brooches and spindle-whorls. Keys, iron weaving-battens and gold bracteates occur as well (fig. 9). Seven of the assemblages with weaponry contained decorated sword equipment, forming a small group of exceptionally rich assemblages. In considering the social context, the idea of the construction of social identity is applied. The small, exclusive group of burials with decorated swords is related to the role of the political leader. The larger group of burials with relief brooches is, with particular reference to the keys, related to the construction of the image and role of the Lady of the house.